Application of The Stimulus-Organism-Response Model in the Airline Industry: Examining Mediating Role of Airline Image in Repurchase Intention - Jawad Ali; Selvan Perumal; Hasnizam Shaari (International Journal of Supply Chain Management, 2020)
The prime objective of the present study is to examine the impact of visual and touch stimuli on repurchase intention. Furthermore, the mediating role of airline image is assessed in the present research as well. The data was collected in the form of questionnaires from the international airline customers of Pakistan airlines travelling from Karachi, Lahore and Islamabad airports. Multi-stage sampling technique was employed for the collection of data. The usable response rate of the questionnaire was 68%. PLS-SEM was used for statistical analysis and hypothesis testing. The findings of the study revealed that touch and visual stimuli have a significant (positive or negative) impact on airline image and repurchase intention. Additionally, airline image also mediates significantly between touch stimuli, visual stimuli and repurchase intention. The findings of the study are essential for the practitioners and policymakers of the airline sector as they can use the study to derive policies regarding customer retention. The study also fills the gap of limited studies regarding the impact of sensory stimuli in the airline sector. Moreover, the study also helps the policy-makers of the airline industry and marketing experts to derive the strategies in order to retain the customers.